Maternal Resilience and Postpartum Depression at the Neonatal Intensive Care Unit - Mautner, Eva; Stern, Christina; Avian, Alexander; Deutsch, Maria; Fluhr, Herbert; Greimel, Elfriede (Frontiers in Pediatrics, 2022)
Background: The neonatal intensive care unit causes maternal stress and postpartum depressive symptoms in preterm and term mothers. Personal resources like maternal resilience are usually not considered in counselling these women. Objective: Evaluation of resilience and differences in postpartum depression after admission of newborns at the neonatal intensive care unit. Methods: This prospective pilot study was conducted in a single teaching hospital in Austria from December 2016 until December 2018. Sixty women completed two internationally validated questionnaires, the Edinburgh Postnatal Depression Scale (EPDS) to evaluate depressive symptoms and the Resilience Scale RS-13 to measure maternal resilience during the postpartum period (three to ten days postpartum). Additionally, women answered two open questions about burdens and relief. Results: Twenty women (34%) showed lower resilience scores. The 39 high-resilient women (66%) showed significantly less depression (p=0.005). Women reported social support from the partner (n=15), from health professionals and psychologists (n=15), family and friends (n=12) and child-specific relief, e.g. spending time with the newborn and involvement in care (n=7) as the most helpful variable during the first postpartum period. Conclusion: The experience of having a newborn at the neonatal intensive care unit is a challenging event for women. Women have different resilience parameters. Mothers with lower resilience will benefit from social support and emotional health promoting activities.